PERTANGGUNGAN KECELAKAAN PENUMPANG ANGKUTAN BERBASIS APLIKASI ONLINE DALAM PERLINDUNGAN DASAR PEMERINTAH - Guntur Rubyantoro Kusumo (JURNAL AKTA YUDISIA, 2021)
ABSTRACT             The development of technology gave birth to a new system in passenger transportation vehicle, one of that development is online-based transportation. The transportation user is increasing, but there was obscured legal relations between passengers, online-based transportation companies and insurance company. Legal certainty of security guarantee, safety and passenger protection to get insurance according to Law Number 33 Year 1964 also vague from social-security context.             This study used normative juridical method. Statute Approach and Conceptual Approach with normative analysis (Content Analysis) used to examine the legal substance that has collected using literature study on the main legal substance sources of Law Number 33 Year 1964 and Law Number 22 Year 2009 .            The results of this research convice that legal relations created between passengers and online-based transportation companies is the conveyance agreement, while the online-based transportation companies with the insurance company is the compulsive insurance, as the premium payer is the online-based transportation companies and the insured is the passenger with State-Owned Enterprise insurance company as the insurer. Guarantee from Law Number 33 Year 1964 given to casualty if the victims get injury or disability, but if they gone, the insurer gave compensation to their heir. The premium amount and passenger insurance was stipulated in Regulation of the Finance Ministry Number 15/PMK/0.10/2017. Insurance scope guarantee from board until debark the online-based transportation. Suicide, vehicle races, accident due to war, and natural disaster makes claim rejected. Insurance expiration is six months from accident, three months since submission, and three months after approval for insurance payments.  Keywords: Coverage, Basic Protection, Onlinse-based Application